Overcoming Research Mistrust in African American Communities by Engaging Community Members as Research Team Members: Challenges and Opportunities - Melissa Ryan; Travaé Hardaway Griffith; Grace Okoro; Tiffany Osborne; Lori Brand Bateman; Janet M. Turan; Raegan W. Durant; Lece Webb; Mona N. Fouad; Gabriela R. Oates (Health Equity)
Objectives: We aimed to understand factors surrounding COVID-19 testing in vulnerable urban and rural African American communities in Alabama, which are characterized by mistrust in medical research. Methods: To address widespread mistrust, we trained lay community members as research coordinators (Community Engagement Coordinators—CECs) and employed them for study recruitment and data collection. We then explored their experiences through group discussions and individual interviews. Results: Ten CECs (8 in Jefferson, 2 in Dallas County; 8 female, 2 male) completed 5 h of instructor-led training followed by virtual Collaborative Institutional Training Initiative (CITI) Human Subjects Training. In 11 weeks, CECs recruited 318 study participants and administered 303 surveys. After survey data collection was completed, CECs recruited survey respondents for participation in focus groups, enrolling 53 individuals. CECs continued their study engagement by reviewing developed study products. Conclusions: Engaging CECs as research personnel facilitated successful completion of planned enrollment with minimal missing data. Investing in communities by training and employing community members as study personnel can help overcome research mistrust and promote support for research and public health interventions.